PERBEDAAN POLA KLINIK TUBERKULOSIS PULMONAL DAN EKSTRA PULMONAL PADA PASIEN USIA DEWASA DAN GERIATRI - Medita Muzwar; Fatur Nur Kholis; Dwi Ngestiningsih (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background: Tuberculosis (TB) is a widespread health problem in the world, including Indonesia. TB infects a wide range of ages, including the elderly. The factors of mortality and morbidity due to TB in Indonesia are caused by inadequate drug using, comorbid disease, and Multi Drug Resistant (MDR) TB. History of symptoms and sign also proper diagnosis are expected to reduce the time delay of TB treatment resulting in lower morbidity.Objective: To determine the difference pattern of clinical pulmonary and extra-pulmonary TB in adult and geriatric patients.Methods: The study design was descriptive analytic. Sample was 225-patient medical records from Dr.Kariadi Hospital Semarang since January until December 2013. Data was described using drawings and tables. Tables used chi-square test to determine differences of variable.Results: 225 samples consisted of 155 patients with pulmonary TB patients (121 adults and 35 elderly), extra pulmonary TB patients 69 (62 adults and 7 elderly). Most symptom of pulmonary TB was shortness of breath (p=0.016) and extra pulmonary TB was weight loss. Results of blood tests found anemia (51.92% pulmonary TB, 42.03% extra pulmonary TB )and lymphopenia (25.00% pulmonary TB, 24.64% extra pulmonary TB). Results of sputum smear tests on pulmonary TB was acid-resistant bacteria (+), while on the extrapulmonary TB was acid-resistant bacteria (-). The thorax x-ray was found radiopaque spots (34.62% of pulmonary TB patients, 1.45% extra pulmonary TB patients). Most comorbid disease with pulmonary TB was another lung disease( 49% of elderly). Length of hospitalization of pulmonary tuberculosis patients was 6-10 days and extra pulmonary TB was more than 15 days. Most complications were hemoptysis and septic shock.Conclusion: The results of this study have almost the same results with the research that has been done before.